1999
DOI: 10.1007/s003830050507
|View full text |Cite
|
Sign up to set email alerts
|

Early repair of inguinal hernia in premature babies

Abstract: Inguinal hernia (IH) is relatively common in premature newborn infants, and the timing of surgical correction is controversial. We studied 40 premature infants who developed an IH and who were initially treated in a neonatal intensive care unit. Birth weight (BW) ranged from 492 to 2,401 g; 21 infants had a BW less than 1,000 g. The weight of the infants at operation ranged from 1,000 to 4,400 g. Twenty-one patients underwent herniotomy within 2 weeks after the diagnosis (short waiting group), in which 1 case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 11 publications
0
28
0
3
Order By: Relevance
“…26 Uemura et al reported comparable inguinal hernia incarceration rates in 19 preterm infants (birth weight range 492-2401 g) who underwent repair at more than 2 weeks after diagnosis, compared with 21 preterm infants who underwent more urgent repair. 27 Although these studies suggest that inguinal hernia repair can be delayed, the data are not as compelling as those suggesting repair on a more urgent basis.…”
Section: Rationale and Timing For Elective Inguinal Hernia Repair In mentioning
confidence: 99%
“…26 Uemura et al reported comparable inguinal hernia incarceration rates in 19 preterm infants (birth weight range 492-2401 g) who underwent repair at more than 2 weeks after diagnosis, compared with 21 preterm infants who underwent more urgent repair. 27 Although these studies suggest that inguinal hernia repair can be delayed, the data are not as compelling as those suggesting repair on a more urgent basis.…”
Section: Rationale and Timing For Elective Inguinal Hernia Repair In mentioning
confidence: 99%
“…Vaos in 2010 [4] and Uemura in 1999 [28] demonstrated that the sooner the patients are operated on upon diagnosis, the lower is the risk of complications. Conversely, Lautz and colleagues [3] recently stated that delaying surgery of newborns and ex-preterms after discharge from the hospital does not increase the risk of complications.…”
Section: Discussionmentioning
confidence: 97%
“…Thirteen were ELWB, 25 were VLBW and 49 were LBW babies. The remaining 67 patients had a birth weight higher than 2,500 g. Median PCA at birth was 36 weeks (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Demographicsmentioning
confidence: 98%
“…[3,14] Thus, Uemura et al as well as Galinier et al recommended that any inguinal hernia diagnosed in an infant should be operated earlier in order to avoid strangulation. [15,16] We have not had cases of strangulated hernia in children. This is due to the fact that children admitted for emergency surgical conditions are often referred to Teaching hospitals because of anesthetic safety.…”
Section: Discussionmentioning
confidence: 99%